Tantangan dan Fenomena Perkembangan Anak dalam Pembelajaran Mendalam pada Jenjang Pendidikan Dasar : Penelitian - Inayatul Ulya; Mochamad Widjanarko; Indah Lestari (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The development of immersive learning in primary education creates opportunities for innovation and complex challenges, particularly those related to children's developmental stages. This article aims to analyze the challenges and phenomena that occur in children's developmental stages in the application of immersive learning in primary education from a cognitive, socio-emotional, and psychological perspective. This article was written using a case study method with a descriptive-qualitative approach, through conceptual analysis and examination of teaching practices in the field. The main idea of ​​this article emphasizes that immersive learning is not only understood as the use of technology in learning, but also as a pedagogical approach that must be adapted to the child's developmental stage. The analysis shows that learning using immersive learning methods has the potential to support meaningful learning and children's holistic development as long as it is planned and structured contextually, gradually, and in accordance with the child's developmental stage. However, implementation that does not consider children's developmental readiness and the teacher's pedagogical role risks causing cognitive overload, psychological stress, and exacerbating socio emotional challenges. The conclusion of this article emphasizes the importance of the teacher's role as a facilitator of child development in immersive learning. Recommendations focus more on strengthening teachers' pedagogical competence, creating a supportive learning environment, and formulating learning policies that are responsive to children's developmental needs in primary education.